2020
DOI: 10.3389/fonc.2020.01513
|View full text |Cite
|
Sign up to set email alerts
|

MiR-3194-3p Inhibits Breast Cancer Progression by Targeting Aquaporin1

Abstract: Increasing evidence indicates that the Aquaporin1 (AQP1) aberrant expression may be related to a wide variety of human cancers, including breast cancer (BC). In the present study, we explore the effects and possible mechanism of miR-3194-3p on the biological behaviors of BC. At first, miR-3194-3p is found to modulate AQP1 expression targeting the 3-UTR using miRNA target prediction algorithms. MiR-3194-3p expression is markedly downregulated, and AQP1 expression is upregulated in BC tissues compared with adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Emerging evidence suggests that miRNAs play important roles in the pathogenesis of many types of human cancers by modulating different genes in the context of signaling pathways involved in tumor promotion or suppression [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence suggests that miRNAs play important roles in the pathogenesis of many types of human cancers by modulating different genes in the context of signaling pathways involved in tumor promotion or suppression [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the important role of miRNAs in the regulation of all essential cellular bioprocesses, including proliferation, differentiation, apoptosis, stress response, and migration [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. MiRNA research has become increasingly attractive as evidence is emerging that miRNAs act as key regulators in the pathogenesis of diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, MCF-7 cells express ER, PR and low levels of HER2 and are used as an in vitro model of hormone-responsive breast cancer types (48). The utilization of these 2 cell lines in experiments allows for the comparison of both breast cancer types (49)(50)(51)(52).…”
Section: Inhibition Of Aquaporins As a Potential Adjunct To Breast Cancer Cryotherapymentioning
confidence: 99%
“…For example, miR-3194-3p is significantly downregulated in hepatocellular carcinoma (HCC) tissues and cells, and miR-3194-3p inhibits the migration, invasion and epithelial-mesenchymal transition (EMT) of HCC cells via suppressing Wnt/β-catenin signaling through targeting BCL9 transcription coactivator (BCL9) [ 25 ]. MiR-3194-3p suppresses cell proliferation, migration, and invasion as well as promotes cell apoptosis in bladder cancer by targeting Aquaporin 1 (AQP1) [ 26 ]. However, the precise mechanisms of miR-3194-3p involvement in tumorigenesis of ERSC remain unclear.…”
Section: Introductionmentioning
confidence: 99%